High morbidity and mortality associated with primary bloodstream infections among pediatric patients with cancer at a Guatemalan tertiary referral hospital - Mukkada, Sheena; Melgar, Mario; Bullington, Craig; Chang, Alicia; Homsi, Maysam R.; Gonzalez, Miriam L.; Antillon, Federico; Su, Yin; Tang, Li; Caniza, Miguela A. (Frontiers in Public Health, 2022)
The heterogeneity of laboratory and clinical infrastructure which exists even in tertiary healthcare facilities around the world poses challenges which may threaten survival outcomes. We performed a 5-year retrospective study of primary bloodstream infections at a dedicated pediatric oncology center in Guatemala. Despite subspecialty support in infectious diseases and critical care, as well as reliable microbiology diagnostics, poor outcomes, including prolonged hospitalization and mortality, were frequent. Our findings suggest that investments in laboratory and clinical data collection are critical to understanding the contributors to poor outcomes and therefore to improving the quality of bloodstream infection management in resource limited settings.